(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the role of Business Information Systems (BIS) in enhancing the level of integration between departments within Libyan institutions, given the administrative and organizational challenges resulting from weak coordination and the reliance of some departments on traditional methods of information exchange. The study stemmed from the problem of inadequate administrative integration and the lack of clarity regarding the effectiveness of implementing BIS, despite the potential these systems offer in improving information flow, standardizing databases, and supporting decision-making. The study also sought to achieve several objectives, most notably evaluating the current state of BIS implementation in Libyan institutions, demonstrating its role in enhancing cooperation and information exchange between departments, improving functional integration, and reducing duplication of work. Furthermore, it aimed to identify the organizational, technical, and human obstacles that limit its effectiveness and propose practical mechanisms for its development to contribute to improving institutional performance efficiency. The study also adopted a descriptive-analytical approach, using a questionnaire as the primary data collection tool. The questionnaire was administered to a stratified random sample of 100 employees from various functional and administrative levels across Libyan institutions. Data were analyzed using the SPSS statistical software, employing several statistical methods including frequencies, percentages, arithmetic means, correlation coefficients, and tests of statistical differences. The results revealed a statistically significant relationship between the use of Business Information Systems (BIS) and the level of integration between departments. These systems contributed to improved administrative coordination, faster information exchange, enhanced decision-making, and reduced duplication and conflict of tasks. The findings also indicated that senior management support, the availability of technological infrastructure, and appropriate employee training are key factors in enhancing the effectiveness of BIS. The study emphasized the importance of BIS as a strategic tool for improving institutional performance in Libyan organizations and offered a set of recommendations to support the activation of these systems and overcome associated obstacles, thereby contributing to better administrative integration and increased efficiency in resource utilization. The study emphasized the importance of BIS as a strategic tool for improving institutional performance in Libyan institutions.